Adaptasi Lingkungan Bisnis Saat Pandemi Covid 19 (Studi Pada UMKM Ledre Di Desa Padangan, Bojonegoro-Jawa Timur) - Yola Amalia, Melisa; Kristina, Anita (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
This study aims to analyze the business environment adaptation of the micro, small and Medium Enterprise (MSME) of ledre in Padangan village. In this research, the writer used qualitative methods of phenomenological studies. The techniques of collecting the data were interviews and documentation. This research used source and theory triangulation, then the data were analyzed and drawn a conclusion. The research results showed there were environmental adaptations of MSME business ledre during the covid-19 pandemic that happened in the work infrastructure environment, namely in the production and distribution processes. The role of the work environment on productivity related to work rules, changing business environment namely norm, business contract, work behavior, mastery of technology, and government policy.